Current Ratio, Debt to Equity Ratio, Total Assets Turnover terhadap Return On Invetment pada PT Unilever Tbk - Indra Ningsih, Nurul Hidayati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to determine the effect of the variables Current Ratio, Debt to Equity Ratio, Total Assets Turnover on Return on Investment. This research was conducted at PT Unilever Tbk for the period 2017-2021. This type of research uses a quantitative approach. Data collection techniques using documentation studies. The data analysis used is multiple linear regression analysis, F test and t test with SPSS 22 for Windows application. The results of the F-test analysis with a significant level of 0.001 is smaller than 0.05, indicating that the model used in this study is suitable for further analysis. The results of the t test show that the Current Ratio and Debt to Equity Ratio have a positive effect on Return on Investment. Meanwhile, Total Assets Turnover has a negative effect on the Return on Investment of PT Unilever Tbk.